2018
DOI: 10.1515/opag-2018-0025
|View full text |Cite
|
Sign up to set email alerts
|

Flower morphological diversity of cinnamon (Cinnamomum verum Presl) in Matara District, Sri Lanka

Abstract: The cinnamon flowers exhibit protogynous dichogamy with 2 flower types “Type A” and “Type B” which first flowers during morning and evening respectively. This floral cycle causes a temporal barrier to the maintenance of elite breeding material and for hybridization with desired parents. Determination of variation in flower and inflorescence morphology can shed light on functional diversity in “Type A” and “Type B” flowers. In order to study these variations, a survey of cultivated cinnamon lands and wild habit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
0
16
0
1
Order By: Relevance
“…Cinnamon ( Cinnamomum verum and Cinnamomum zeylanicum ) is one of the plants that belong to the Lauraceae family. This traditional herbal medicine is from Australia and Asia [ 118 , 119 , 120 ]. Based on the antioxidant, antimicrobial, and anticarcinogenic activities of this plant, it is widely used in medical industries [ 120 , 121 , 122 , 123 ].…”
Section: Antimicrobial Agentmentioning
confidence: 99%
“…Cinnamon ( Cinnamomum verum and Cinnamomum zeylanicum ) is one of the plants that belong to the Lauraceae family. This traditional herbal medicine is from Australia and Asia [ 118 , 119 , 120 ]. Based on the antioxidant, antimicrobial, and anticarcinogenic activities of this plant, it is widely used in medical industries [ 120 , 121 , 122 , 123 ].…”
Section: Antimicrobial Agentmentioning
confidence: 99%
“…Kumarathilake (2012) developed a key for the identification of Sri Lankan Cinnamomum species based only on morphological characteristics including characteristics of immature bark. Recently, Azad and colleagues reported that some leaf morphological traits are age and environment independent (Azad et al, 2016). Consequently, the objective of the present study was to develop a morphological index and a practical botanical key for field-level identification of different Cinnamomum species present in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%
“…Currently accepted species classification and identification of Cinnamomum are purely based on morphological traits such as leaf arrangement, flush color, leaf shape, apex and venation [20,21]. While C. litseifolium, C. citriodorum, C. sinharajaense, and C. capparu-coronde are easily distinguishable using leaf morphological traits, identification of others, such as C. rivulorum and C. dubium are not that straightforward [22].…”
Section: Introductionmentioning
confidence: 99%